The Potential Utilization of Oil Palm Production Waste at PT. Tata Hamparan Eka Persada - Ramadhanti, Debby; Puriza, Muhammad Yonggi; Sunanda, Wahri (International Journal of Electrical, Energy and Power System Engineering, 2023)
Oil palm (Elaeis guineensis Jacq.) is one of the commodities that is expected to increase the economic income of the community, especially plantation farmers. The palm oil industry in Bangka district in 2020 is 41.88 thousand tons. The production process of crude palm oil produces waste that has the potential to pollute the environment, namely solid waste and liquid waste. Palm oil mill effluent (POME) contains methane gas (CH4) which has the potential to be a source of energy that can be processed into biogas and solid waste in the form of shells, fiber, EFB has the potential to become biomass. The results obtained from the calculation of the total power that can be generated for 2.5 years of liquid waste (POME) is 6.9462 MW in the category of high heat waste, followed by solid waste (TKS) of 1.4881 MW, fiber waste of 0.9864 MW and shell waste of 0.5646 MW. The total CO2 emissions generated from the generator for 2.5 years for solid waste are 73893.63 tons of CO2 in the category of high-heat waste, and for liquid waste, it is 65867.09 tons of CO2.